2018
DOI: 10.1186/s12966-018-0695-z
|View full text |Cite
|
Sign up to set email alerts
|

Is objectively measured light-intensity physical activity associated with health outcomes after adjustment for moderate-to-vigorous physical activity in adults? A systematic review

Abstract: BackgroundAn increasing number of studies have demonstrated that light-intensity physical activity (LPA) confers health benefits after adjustment for moderate-to-vigorous physical activity (MVPA). The purpose of this systematic review was to summarize existing epidemiological evidence on associations of objectively measured LPA with health outcomes in adults.MethodsThis review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We searched on PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 57 publications
4
129
0
Order By: Relevance
“…The subgroup analyses and metaregression analyses both confirmed that more time spent in LPA was inversely associated with mortality risks, supporting previous systematic reviews and meta-analysis for general populations. 5,8,9,47 The present meta-analyses showed progressive decreases in mortality risk as people spend more time in LPA. Compared with the lowest LPA group, the risk of death decreased approximately 35% and 50% for participants spending between 5 and 7 h/d and more than 7 hours a day in LPA, respectively (Model 2 in Table 1).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…The subgroup analyses and metaregression analyses both confirmed that more time spent in LPA was inversely associated with mortality risks, supporting previous systematic reviews and meta-analysis for general populations. 5,8,9,47 The present meta-analyses showed progressive decreases in mortality risk as people spend more time in LPA. Compared with the lowest LPA group, the risk of death decreased approximately 35% and 50% for participants spending between 5 and 7 h/d and more than 7 hours a day in LPA, respectively (Model 2 in Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…These search terms were utilized based on previous studies. 5,9 The reference lists of all selected articles were also screened for eligible records.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…10 In addition, the adverse health effects and mortality risk associated with time spent in sedentary behavior (SB), for example, activities with <1, 5 MET, has been highlighted. [11][12][13] Still, most studies have separately investigated the effect of movement behaviors such as SB, LIPA, and MVPA as independent entities, [14][15][16] and not considered that the portions of time spent on each activity represent relative information of the complete day. Recent evidence suggest that time spent in different behaviors are related, and thus, time use in one behavior also depends on the time it displaced from another The association between the composition of movement behaviors and mortality risk, acknowledging the composition nature of daily time data, is limited explored.…”
Section: Introductionmentioning
confidence: 99%